Systemic Relapse in a Young Adult Patient with Primary CNS Diffuse Large B-Cell Lymphoma - Khorasanchi, Adam; Benson, Zachary; Hall, Misty; Ebadirad, Nelya; Gharavi, Mohammad H.; Willard, Patrick; Chimzar, Miranda; McKay, John; Simmons, Gary; Yazbeck, Victor (Case Reports in Hematology, 2022)
Primary central nervous system diffuse large B-cell lymphoma (PCNS-DLBCL) is a rare form of non-Hodgkin’s lymphoma, characterized by an aggressive disease course. While CNS relapse is common, systemic relapse is rare with no consensus on optimal treatment. This paper presents an unusual case of advanced PCNS-DLBCL with systemic relapse, including adrenal gland involvement. A review of the existing literature and a discussion on the management of systemic relapse in PCNS-DLBCL is also provided.